Experimental study of the influence of different hole-forming methods on the bearing characteristics of post-grouting pile in Loess Areas. (March 2021) - Zhou, Zhijun; Xu, Fu; Lei, Jiangtao; Bai, Yang; Chen, Chaoran; Xu, Tianyu; Zhang, Zhipeng; Zhu, Linxuan; Liu, Tong
Abstract: This paper studies the bearing characteristics of different types of cast-in-place piles, with or without grouting, based on a bridge construction in Wuqi-Dingbian Expressway. Manual digging piles (MDPs), rotary drilling piles (RDPs), and impact drilling piles (IDPs) are investigated, and an in-situ static load test is carried out on each type of hole-forming method. The post-grouting results show that the grouting quantity of RDP is the largest, which is 3.15 t, and the IDP is the smallest, which is 1.5 t. According to the static load test, the ultimate bearing capacity of IDP is the largest and increases the most after grouting, while MDP has the smallest increase in ultimate bearing capacity. The IDP also displays the most significant increase of pile side resistance and largest proportion of pile end resistance to the total load, showing obvious characteristics of the end bearing friction pile. The calculation method of ultimate bearing capacity of the post-grouting pile recommended by Chinese code is also verified in this work, illustrating that it is necessary to study the upper return height of slurry in post-grouting. The obtained research results provide an increased understanding of the post-grouting mechanism and reference for the rational calculation of the bearing capacity of post-grouting pile and hole-forming method selection.